I. Turgenev’s novel “Rudin” in Chinese literary studies - Siwen Guo (RUDN Journal of Studies in Literature and Journalism, 2019)
The work of I. Turgenev was translated into Chinese in the first half of the twentieth century and later spread widely in China, having a great influence on the new generation of Chinese writers. At the same time, more and more literary critics began to study the works of Turgenev. Extensive research and analysis, as well as the study of works from different angles, contributed to a better understanding of Turgenev and Russian literature by Chinese readers. The article discusses the publications of Chinese litterateurs and critics from the second half of the 20th to beginning of the 21st century, the work of Ivan Sergeevich Turgenev, notes the enduring interest of the Chinese audience to the work of Russian prose writer, in particular, to the novel “Rudin”. Special attention is paid to the prose writer's “path” to the novel; it is proved that the high interest of scientists to Dmitry Rudin, the protagonist of this novel, caused by Chinese specifics and the relevance of many problems associated with this image. The article explains the evolution of the attitude of the Chinese to Rudin: from agreement with Russian researchers considering him as a superfl person to disagreement with them. At the same time, Rudin is compared with typically similar images in Chinese literature. An analysis of Turgenev's works by Chinese literary critics will provide detailed information for future studies in international literary circles, and can also lay the foundation for finding differences between Chinese and Russian literary criticism.